THE ASSESSMENT OF THE DIAGNOSTIC ACCURACY OF HYPERLACTATEMIA IN PREDICTING MORTALITY IN PATIENTS WITH SECONDARY PERITONITIS (The Research of Medical Science Review, 2025)
INTRODUCTION: Serial lactate measurement is found to predict mortality in septic shock. Majority of patients with peritonitis for emergency laparotomy are in sepsis and mortality rate is substantial. However, lactate dynamics has not been studied in this patient population. OBJECTIVE: To determine the diagnostic accuracy of hyperlactatemia in predicting the 28-days mortality of patientswith secondary peritonitis. STUDY DESIGN: Descriptive cross sectional study. STUDY SETTING: Study was conducted at Department ofGeneral Surgery, Dr. Ruth K.M Pfau Civil Hospital Karachi DURATION OF STUDY: Six months after approval of synopsisfrom 07-06-22 till 07- 12-22. SUBJECTS AND METHODS: Quantitative and qualitative data was collected, presented and analyzed. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of hyperlactatemia for the prediction of mortality was calculated. RESULTS: A total of 108 patients who met the inclusion and exclusion criteria were included in this study. Mean age, height, weight, BMI and duration of hospital stay in our study was44.23±13.57 years, 26.72±1.56 kg/m2 158±7.28 cm, 78.7±9.87 kg and 9.08±5.51 days. 49 (45.4%) were male and 59(54.6%) were female. Out of 108 patients, sensitivity, specificity,positive predictive value, negative predictive value and diagnostic accuracy of hyperlactatemia for the prediction of mortality was found to be 94.2%, 69.8%, 60%, 96.2% and 77.7% respectively. CONCLUSION: Preoperative, immediate postoperative and 24-h postoperative lactate value independently predict 28-daymortalityin peritonitis patients undergoing emergency laparotomy.